Prevalence and Correlates of Sex Selling and Sex Purchasing among Adults Seeking Treatment for Cocaine Use Disorder. (6th December 2021) - Lathan, Emma C.; Hong, Judy H.; Heads, Angela M.; Borgogna, Nicholas C.; Schmitz, Joy M.
Abstract: Introduction : Exchange sex places individuals with cocaine use disorder (CUD) at particularly high risk for deleterious safety and health outcomes. A substance use treatment provider who is aware of a patient's exchange sex behavior is better able to provide appropriate screening, care, and/or referral to risk reduction services. However, little is known about exchange sex, especially purchasing, among treatment-seeking adults with CUD. Method : The current study examined the prevalence and correlates of sex selling and sex purchasing among treatment-seeking men and women with CUD ( n  = 109; ClinicalTrials.gov #NCT02896712). Separate binary logistic regressions via backward elimination were used to identify best fitting models for sex selling and sex purchasing. Results : Over 41% of participants endorsed exchange sex within the last 30 days; 20.2% reported selling sex and 30.3% reported purchasing sex. Sex selling and sex purchasing rates differed by gender and race. Number of sexual partners (OR = 5.83, 95% CI = 2.07–16.43), concern about contracting HIV/AIDS (OR = 2.01, 95% CI = 1.31–3.44), cumulative interpersonal trauma exposure (OR = 1.82, 95% CI = 1.20–2.77), years using cocaine (OR = 1.11, 95% CI = 1.03–1.20), drug-related problem days (OR = 1.07, 95% CI = 1.00–1.14), and sexual preference (OR = 9.50, 95% CI = .69–130.35) were retained in the final model estimating sex selling (Nagelkerke R 2 = .56). In the final sex purchasing model (Nagelkerke R 2 = .46), gender (OR = 36.17, 95% CI = 2.96–441.75), number of sexual partners (OR = 6.28, 95% CI = 2.69–14.66), number of convictions (OR = 1.13, 95% CI = 1.02–1.25), and drug-related problem days (OR = 0.96, 95% CI = .92–1.01) were retained. Conclusion : Predictive models in this study identified distinct sets of variables related to sex selling and purchasing. Findings may be used to improve identification of exchange sex in the substance use treatment setting and referral to targeted interventions to reduce associated risk.